Testing the Independent and Joint Contribution of Exposure to Neurodevelopmental Adversity and Childhood Trauma to Risk of Psychotic Experiences in Adulthood - Liu, Yiwen (Schizophr Bull, 2020)
Exposure to neurodevelopmental adversity and childhood trauma are both independently associated with psychosis. However, there is little research on the mechanism underlying their relationship with each other. The current study investigated both the independent and joint effects of neurodevelopmental adversity and childhood trauma to better understand the etiology of psychosis. A large population-based cohort (N = 3514) followed from birth was assessed on psychotic experiences (PE) at 24 years. Neurodevelopmental adversity included obstetric complications (birth weight, gestational age, in-utero influenza exposure, resuscitation) and developmental impairment (cognitive and motor impairments). Trauma exposure included caregiver and peer inflicted trauma up to 17 years. Multiple regression models tested their independent and interactive effect on PE, and path analysis estimated the indirect effect of neurodevelopmental adversity on PE via trauma. Neurodevelopmental adversity (OR = 1.32, 95%CI: 1.08–1.62) and trauma (OR = 1.97, 95%CI: 1.65–2.36) independently increased the odds of PE. There was also an indirect relationship between neurodevelopmental adversity and PE via increased exposure to childhood trauma (β = 0.01, 95%CI: 0.004–0.024). In particular, peer bullying mediated the association between developmental impairment to PE (β = 0.02, 95%CI: 0.01–0.03). In conclusion, children with neurodevelopmental adversity, in particular those with developmental impairment, are more likely to be exposed to trauma. This new etiological understanding of psychosis suggests that PE may be partially modifiable through reducing exposure to peer bullying, especially in children with developmental impairment.